PENGEMBANGAN SISTEM INFORMASI PENELITIAN DAN PENGABDIAN DOSEN JURUSAN ILMU KOMPUTER MENGGUNAKAN METODE RATIONAL UNIFIED PROCESS (RUP) - Rico Andrian; Dwi Sakethi; Muhammad Chairuddin (Universitas Lampung, 2014)
AbstractBesides providing the education, a lecturer has an obligation to carry out the research and dedication for society. Research and dedication were one of requirements to increase the lecturers’ functional position and as an assessment reference of department accreditation. Data processing of lecturers’ research and dedication in Computer Science Department used a spreadsheet. The use of spreadsheets thas been able to process the data of the research and dedication well, but it less according to time and resource efficiency. This study was conducted to develop information systems of lecturers’ research and dedication in Computer Science Department as a management tool of department in data processing of lecturers’ research and dedication. System development method that is used is the Rational Unified Process (RUP). RUP is a collection of best practices from software development industry. RUP has six mains workflow those are business modeling, requirements, analysis and design, implementation, testing, and deployment. Lecturers’ research and dedication information systems in Computer Science Department has been developed using the RUP. RUP method provided flexibility to the programmer in develeoping software.Keywords: dedication, information systems, lecturer, research, rup.